Preparación de láminas delgadas de suelos arcillosos por impregnación con metacrilato de metilo - Paseyro, J.; Balcar, J. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Methyl-metacrylate, a chemical of low vis cosity, easily penetrates in the smaller pores of clayey soils and polymerizes under the influence of gamma ra diations (1 Mrad) so that the impregnated soil becomes apt for preparation of thin sections Radiation does not cause any changes in the minerals that would difficult their identification